Preparation method of high-elasticity and high-hardness rubber composite material
By using specific components and processes in rubber composite materials, the problem of difficult balance between high elasticity and high hardness in rubber composite materials in the prior art is solved, and the improvement of material performance and the expansion of application fields is achieved.
Patent Information
- Application Number
- CN202411881151.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to achieve a balance between high elasticity and high hardness in rubber composites, limiting the application of rubber in certain specific fields.
Components such as ethylene propylene ternary rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene and inorganic fillers (such as zinc oxide, silica lime powder and alumina) are used to ensure uniform dispersion and cross-linking reaction of components through premixing, extrusion granulation and vulcanization treatment.
The high elasticity and hardness of rubber composite materials are achieved, and the overall performance of the materials is improved, making it more widely used in different fields.
Smart Images

Figure BDA0005198233410000131 
Figure BDA0005198233410000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber materials, and in particular to a method for preparing a high-elasticity and high-hardness rubber composite material. Background Art
[0002] As a necessary material for manufacturing aircraft, warships, automobiles, tractors, harvesters, irrigation and drainage machinery, medical equipment, etc., rubber has always attracted much attention for its performance and application range. According to different sources, rubber can be divided into natural rubber and synthetic rubber. Although synthetic rubber is often not as comprehensive as natural rubber in terms of performance, it has high elasticity, insulation, air tightness, oil resistance, high or low temperature resistance and other properties, so it is widely used in industry, agriculture, national defense, transportation and daily life.
[0003] In the preparation process of rubber composites, the uniformity of raw material dispersion, the interfacial adhesion level between fiber and rubber matrix, and the mechanical properties of rubber materials are all key factors. Traditional preparation methods often make it difficult to evenly disperse raw materials in the rubber matrix, resulting in limited performance of rubber composites.
[0004] Patent CN102731889B provides a high-hardness and high-elasticity ionized resin and its preparation method. Its composition includes (expressed in wt.%), polyethylene: 10-20%, ethylene octene elastomer: 40-50%, methacrylic acid: 10-15%, white carbon black: 5-10%, zinc oxide: 10-15%, zinc stearate: 1-2%, initiator 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane: 0.5-1%. The ionized resin has a hardness (Shore A) of more than 95, a rebound resilience of more than 60%, and a tensile strength of more than 15MPa. The resin can be used in combination with various rubbers to increase the hardness of rubber products, and can also increase elasticity, while improving the processing performance of the rubber compound. It can also be used in combination with various plastics to improve its toughness.
[0005] However, the elasticity and hardness of the rubber prepared by the prior art are not fully improved, which limits the application of rubber in certain specific fields. Therefore, developing a rubber composite material with high elasticity and high hardness has become a hot topic in current research. Based on this, the present invention proposes a preparation method of a high elasticity and high hardness rubber composite material. Summary of the invention
[0006] The purpose of the invention is to provide a method for preparing a high-elasticity and high-hardness rubber composite material.
[0007] The invention provides a preparation method of a high-elasticity and high-hardness rubber composite material, which comprises the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene and inorganic filler at room temperature for 2-3 minutes; slowly adding zinc stearate, carbon black, accelerator, sulfur and modified paraffin wax to the premix within two minutes, mixing at room temperature for 6-8 minutes to ensure uniform dispersion; extruding and granulating the mixed materials at an extrusion temperature of 170-180°C, and vulcanizing the extruded particles at a temperature of 150-160°C for 15-20 minutes to obtain the composite material.
[0008] Furthermore, the weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is (90-100): (26-30): (20-22): (12-16): (1.5-2.5): (180-190): (3-4): (0.7-1): (15-20): (15-17).
[0009] Furthermore, the inorganic filler comprises zinc oxide, silica lime powder and aluminum oxide in a weight ratio of (2-3): (10-12): (5-7).
[0010] Furthermore, the preparation method of the modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 80-90° C. for 40-50 minutes, then adding paraffin and stirring for 8-10 minutes, adding emulsifier and continuing stirring for 20-30 minutes, and cooling to obtain the modified paraffin.
[0011] Furthermore, the weight ratio of the montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is (6-8): (70-80): (2-3): (16-18): (0.5-1).
[0012] Furthermore, the emulsifier is emulsifier 503.
[0013] Furthermore, the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of (1-2):(3-4):(1-2).
[0014] Furthermore, the thermoplastic polyester elastomer model is TH3055.
[0015] Furthermore, the molecular weight of the low molecular weight polyethylene is 5000-10000.
[0016] Furthermore, the carbon black is carbon black N762.
[0017] The beneficial effects of the present invention are:
[0018] The high elasticity of rubber mainly comes from the long-chain polymer compounds in its molecular structure, and these molecular chains have great flexibility and mobility. In the present invention, EPDM, nitrile rubber and thermoplastic polyester elastomer all possess such molecular structure characteristics. The linear or branched polymer chains they contain can be stretched under external force, and can quickly recover the curling and shrinking shape after the external force is removed, thereby producing high elasticity. The addition of low molecular weight polyethylene also helps to improve the elasticity of the material. Although the low molecular weight part has an adverse effect on strength, it plays a role similar to plasticizer in the present invention, increases the plasticity and mobility of the molecular chain, thereby further improving elasticity.
[0019] Zinc oxide, silica lime powder and alumina are used as inorganic fillers in EPDM rubber, nitrile rubber and thermoplastic polyester elastomers. The filler particles play a physical supporting and reinforcing role in the rubber matrix. These particles have a high specific surface area and surface energy, and can interact strongly with the rubber molecular chains, thereby increasing the strength of the rubber matrix. The uniform dispersion of filler particles in the rubber helps to form a more compact network structure, which can better resist deformation when subjected to external forces, thereby increasing the hardness of the rubber. Inorganic fillers such as alumina and silica lime powder have high rigidity and hardness. Their addition can significantly improve the overall rigidity of the rubber composite material, so that the material can better maintain shape stability when subjected to external forces and is not prone to permanent deformation. Zinc oxide plays the role of a vulcanization activator in the rubber vulcanization process, which can accelerate the cross-linking reaction between rubber molecular chains. This cross-linking reaction can form a more compact network structure, thereby increasing the hardness and strength of the rubber. Although inorganic fillers such as silica lime powder and alumina do not directly participate in the cross-linking reaction, their presence can affect the movement and arrangement of rubber molecular chains, thereby indirectly affecting the progress and degree of cross-linking reaction.
[0020] In addition, the addition of inorganic fillers will restrict the movement of rubber molecular chains. This restriction makes it more difficult for rubber molecular chains to slide and orient on a large scale when subjected to external forces, thereby increasing the rigidity of the material. The interaction between inorganic fillers and the rubber matrix and the restriction of the movement of rubber molecular chains by filler particles jointly determine the hardness and elasticity of the rubber composite material. By adjusting parameters such as the type, amount and degree of dispersion of the filler, a balance between hardness and elasticity can be achieved. Among them, silica lime powder, as an inorganic filler, has a high specific surface area and excellent dispersibility, and can be evenly filled in the rubber matrix. Increasing the amount of aluminum oxide and silica lime powder can increase the hardness of the material; while increasing the amount of zinc oxide can promote the cross-linking reaction and improve the elastic recovery ability of the material. When the three are compounded, in addition to the aforementioned individual effects, the three can form a more compact and stable structure in the rubber matrix after compounding, which jointly enhances the high elasticity and high hardness of the rubber composite material.
[0021] The present invention utilizes montmorillonite to modify paraffin, wherein the paraffin component has certain flexibility, can play a lubricating and buffering role between rubber molecular chains, thereby slowing down the breakage and destruction of rubber molecular chains when subjected to external forces; and paraffin and montmorillonite are filled in the rubber matrix together, increasing the density and strength of the rubber; and the silane coupling agent KH560 enhances the interaction between the inorganic filler and the rubber matrix, making the composite material more compact and stable. After the montmorillonite is modified, its layered structure is maintained, and the surface properties are improved, and the compatibility with the rubber matrix is enhanced. The modified paraffin can fill the gaps between rubber molecules, forming a physical barrier to prevent the expansion of cracks, thereby improving the hardness and elasticity of the rubber.
[0022] The synergistic effect of the paraffin modified by montmorillonite with zinc oxide, silica lime powder and aluminum oxide as inorganic fillers in the present invention achieves the effects of high elasticity and high hardness in the rubber composite material, mainly due to the individual effects of each component and the synergistic effect between them. This synergistic effect enables the rubber composite material to have higher hardness and strength while maintaining high elasticity, thereby meeting the requirements for the performance of rubber composite materials in different fields. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] The present embodiment provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding the mixed material into granules at an extrusion temperature of 175° C., and vulcanizing the extruded granules at a temperature of 155° C. for 17.5 minutes to obtain the composite material;
[0026] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 95:28:21:14:2:185:3.5:0.85:17.5:16;
[0027] The inorganic filler includes zinc oxide, silica lime powder and aluminum oxide in a weight ratio of 2.5:11:6; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0028] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 85°C for 45 minutes, then adding paraffin and stirring for 9 minutes, adding emulsifier and continuing stirring for 25 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 7:75:2.5:17:0.75; the emulsifier is emulsifier 503.
[0029] Example 2
[0030] The present embodiment provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 8 minutes to ensure uniform dispersion; extruding the mixed material into granules at an extrusion temperature of 170° C., and vulcanizing the extruded granules at a temperature of 160° C. for 15 minutes to obtain the composite material;
[0031] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 100:26):22:12:2.5:180:4:0.7:20:15;
[0032] The inorganic filler includes zinc oxide, silica lime powder and aluminum oxide in a weight ratio of 2:12:5; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 2:3:2; the thermoplastic polyester elastomer model is TH3055; the average molecular weight of the low molecular weight polyethylene is 5000; the carbon black is carbon black N762;
[0033] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 90°C for 40 minutes, then adding paraffin and stirring for 10 minutes, adding emulsifier and continuing stirring for 20 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 8:70:3:16:1; the emulsifier is emulsifier 503.
[0034] Example 3
[0035] The present embodiment provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 3 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 6 minutes to ensure uniform dispersion; extruding the mixed material into granules at an extrusion temperature of 180° C., and vulcanizing the extruded granules at a temperature of 150° C. for 20 minutes to obtain the composite material;
[0036] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 90:30:20:16:1.5:190:3:1:15:17;
[0037] The inorganic filler includes zinc oxide, silica lime powder and aluminum oxide in a weight ratio of 2:12:5; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 2:3:2; the thermoplastic polyester elastomer model is TH3055; the average molecular weight of the low molecular weight polyethylene is 10000; the carbon black is carbon black N762;
[0038] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 80°C for 50 minutes, then adding paraffin and stirring for 8 minutes, adding emulsifier and continuing stirring for 30 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 6:80:2:18:0.5; the emulsifier is emulsifier 503.
[0039] Example 4
[0040] The present embodiment provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 6 minutes to ensure uniform dispersion; extruding the mixed material into granules at an extrusion temperature of 170° C., and vulcanizing the extruded granules at a temperature of 150° C. for 15 minutes to obtain the composite material;
[0041] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 90:26:20:12:1.5:180:3:0.7:15:15;
[0042] The inorganic filler includes zinc oxide, silica lime powder and aluminum oxide in a weight ratio of 2:10:5; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1:3:1; the thermoplastic polyester elastomer model is TH3055; the average molecular weight of the low molecular weight polyethylene is 6000; the carbon black is carbon black N762;
[0043] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 80°C for 40 minutes, then adding paraffin and stirring for 8 minutes, adding emulsifier and continuing stirring for 20 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 6:80:3:18:1; the emulsifier is emulsifier 503.
[0044] Comparative Example 1
[0045] The present comparative example provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and paraffin to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding the mixed material into granules at an extrusion temperature of 175° C., and vulcanizing the extruded granules at a temperature of 155° C. for 17.5 minutes to obtain the obtained material;
[0046] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 95:28:21:14:2:185:3.5:0.85:17.5:16;
[0047] The inorganic filler includes zinc oxide, silica lime powder and aluminum oxide in a weight ratio of 2.5:11:6; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0048] Comparative Example 2
[0049] The present comparative example provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, and sulfur to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding and granulating the mixed material at an extrusion temperature of 175° C., and vulcanizing the extruded particles at a temperature of 155° C. for 17.5 minutes to obtain the obtained material;
[0050] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator and sulfur is 95:28:21:14:2:185:3.5:0.85:17.5;
[0051] The inorganic filler includes zinc oxide, silica lime powder and aluminum oxide in a weight ratio of 2.5:11:6; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0052] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 85°C for 45 minutes, then adding paraffin and stirring for 9 minutes, adding emulsifier and continuing stirring for 25 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 7:75:2.5:17:0.75; the emulsifier is emulsifier 503.
[0053] Comparative Example 3
[0054] The present comparative example provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding and granulating the mixed material at an extrusion temperature of 175° C., and vulcanizing the extruded particles at a temperature of 155° C. for 17.5 minutes to obtain the composite material;
[0055] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 95:28:21:14:2:185:3.5:0.85:17.5:16;
[0056] The inorganic filler includes silica lime powder and alumina in a weight ratio of 11:6; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0057] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 85°C for 45 minutes, then adding paraffin and stirring for 9 minutes, adding emulsifier and continuing stirring for 25 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 7:75:2.5:17:0.75; the emulsifier is emulsifier 503.
[0058] Comparative Example 4
[0059] The present comparative example provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding and granulating the mixed material at an extrusion temperature of 175° C., and vulcanizing the extruded particles at a temperature of 155° C. for 17.5 minutes to obtain the composite material;
[0060] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 95:28:21:14:2:185:3.5:0.85:17.5:16;
[0061] The inorganic filler includes zinc oxide and aluminum oxide in a weight ratio of 2.5:6; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0062] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 85°C for 45 minutes, then adding paraffin and stirring for 9 minutes, adding emulsifier and continuing stirring for 25 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 7:75:2.5:17:0.75; the emulsifier is emulsifier 503.
[0063] Comparative Example 5
[0064] The present comparative example provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding and granulating the mixed material at an extrusion temperature of 175° C., and vulcanizing the extruded particles at a temperature of 155° C. for 17.5 minutes to obtain the composite material;
[0065] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 95:28:21:14:2:185:3.5:0.85:17.5:16;
[0066] The inorganic filler includes zinc oxide and silica lime powder in a weight ratio of 2.5:11; the accelerator includes accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0067] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 85°C for 45 minutes, then adding paraffin and stirring for 9 minutes, adding emulsifier and continuing stirring for 25 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 7:75:2.5:17:0.75; the emulsifier is emulsifier 503.
[0068] Comparative Example 6
[0069] The present comparative example provides a method for preparing a high-elasticity and high-hardness rubber composite material, comprising the following steps: premixing EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, and inorganic filler at room temperature for 2.5 minutes; then slowly adding zinc stearate, carbon black, accelerator, sulfur, and modified paraffin wax to the premix within two minutes, and mixing at room temperature for 7 minutes to ensure uniform dispersion; extruding and granulating the mixed material at an extrusion temperature of 175° C., and vulcanizing the extruded particles at a temperature of 155° C. for 17.5 minutes to obtain the composite material;
[0070] The weight ratio of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin is 95:28:21:14:2:185:3.5:0.85:17.5:16;
[0071] The inorganic filler is silica lime powder; the accelerators include accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of 1.5:3.5:1.5; the thermoplastic polyester elastomer model is TH3055; the evaluation molecular weight of the low molecular weight polyethylene is 8000; the carbon black is carbon black N762;
[0072] The preparation method of modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 85°C for 45 minutes, then adding paraffin and stirring for 9 minutes, adding emulsifier and continuing stirring for 25 minutes, and cooling to obtain the modified paraffin; the weight ratio of montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is 7:75:2.5:17:0.75; the emulsifier is emulsifier 503.
[0073] The rubber composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were tested;
[0074] (1) Hardness: Tested in accordance with the national standard GB / T6031;
[0075] (2) Tensile strength: tested in accordance with the national standard GB / T528, unit: MPa;
[0076] (3) Elongation at break: tested according to GB / T528 standard, unit: %;
[0077] (4) Resilience: tested according to the national standard GB / T1681, unit: %;
[0078] The test results are shown in Table 1 below:
[0079] Table 1
[0080]
[0081]
[0082] Finally, it should be noted that: the applicant declares that the present invention uses the above-mentioned embodiments to illustrate the products and detailed preparation methods of the present invention, but the present invention is not limited to the above-mentioned products and detailed preparation methods, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials of the products of the present invention and the addition of auxiliary materials, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0083] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments, and the technical solution of the present invention can be subjected to a variety of simple modifications within the technical concept of the present invention. These simple modifications all belong to the protection scope of the present invention.
[0084] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0085] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a high elasticity and high hardness rubber composite material, characterized in that the steps include: Premix EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene and inorganic filler at room temperature for 2-3 minutes; then slowly add zinc stearate, carbon black, accelerator, sulfur and modified paraffin into the premix within two minutes, mix at room temperature for 6-8 minutes to ensure uniform dispersion; extrude the mixed material into granules at an extrusion temperature of 170-180°C, and vulcanize the extruded granules at a temperature of 150-160°C for 15-20 minutes.
2. The method for preparing a high-elasticity and high-hardness rubber composite material according to claim 1, characterized in that: The weight ratios of the EPDM rubber, nitrile rubber, thermoplastic polyester elastomer, low molecular weight polyethylene, inorganic filler, zinc stearate, carbon black, accelerator, sulfur and modified paraffin are (90-100): (26-30): (20-22): (12-16): (1.5-2.5): (180-190): (3-4): (0.7-1): (15-20): (15-17).
3. The method for preparing a high elasticity and high hardness rubber composite material according to claim 1, characterized in that: The inorganic filler comprises zinc oxide, silica lime powder and aluminum oxide in a weight ratio of (2-3): (10-12): (5-7).
4. The method for preparing a high elasticity and high hardness rubber composite material according to claim 1, characterized in that: The preparation method of the modified paraffin comprises: dispersing montmorillonite in deionized water, adding silane coupling agent KH560, stirring at 80-90° C. for 40-50 minutes, then adding paraffin and stirring for 8-10 minutes, adding emulsifier and continuing stirring for 20-30 minutes, and cooling to obtain the modified paraffin.
5. The method for preparing a high elasticity and high hardness rubber composite material according to claim 4, characterized in that: The weight ratio of the montmorillonite, deionized water, silane coupling agent KH560, paraffin and emulsifier is (6-8): (70-80): (2-3): (16-18): (0.5-1).
6. The method for preparing a high elasticity and high hardness rubber composite material according to claim 4, characterized in that: The emulsifier is emulsifier 503.
7. The method for preparing a high elasticity and high hardness rubber composite material according to claim 1, characterized in that: The accelerators include accelerator TMTD, accelerator DM and accelerator BZ in a weight ratio of (1-2):(3-4):(1-2).
8. The method for preparing a high elasticity and high hardness rubber composite material according to claim 1, characterized in that: The thermoplastic polyester elastomer model is TH3055.
9. The method for preparing a high elasticity and high hardness rubber composite material according to claim 1, characterized in that: The molecular weight of the low molecular weight polyethylene is 5000-10000.
10. The method for preparing a high elasticity and high hardness rubber composite material according to claim 1, characterized in that: The carbon black is carbon black N762.
Citation Information
Patent Citations
Ionized resin with high hardness and high elasticity, and preparation method thereof
CN102731889B